Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5770/cgj.17.100
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the SIMARD MD to Clinical Impression in Assessing Fitness to Drive in Patients with Cognitive Impairment

Abstract: BackgroundThe assessment of fitness to drive in patients with cognitive impairment is complex. The SIMARD MD was developed to assist with assessing fitness to drive. This study compares the clinical decision made by a geriatrician regarding driving with the SIMARD MD score.MethodsPatients with a diagnosis of mild dementia or mild cognitive impairment, who had a SIMARD MD test, were included in the sample. A retrospective chart review was completed to gather diagnosis, driving status, and cognitive and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In many jurisdictions, physicians are responsible for determining and reporting on medical fitness to drive, yet the research shows that they are often not comfortable assessing driving safety because they lack the appropriate tools and guidelines to do so confidently. 57 59 Although follow-up research is needed, these results suggest that measures of attention and visual processing could be particularly useful for professionals who are often responsible for determining fitness to drive, yet lack the instruments that would allow them to identify specific cognitive and visual deficits related to driving with exactitude. The exploration and identification of such tools will aid professionals to comfortably make this determination.…”
Section: Discussionmentioning
confidence: 99%
“…In many jurisdictions, physicians are responsible for determining and reporting on medical fitness to drive, yet the research shows that they are often not comfortable assessing driving safety because they lack the appropriate tools and guidelines to do so confidently. 57 59 Although follow-up research is needed, these results suggest that measures of attention and visual processing could be particularly useful for professionals who are often responsible for determining fitness to drive, yet lack the instruments that would allow them to identify specific cognitive and visual deficits related to driving with exactitude. The exploration and identification of such tools will aid professionals to comfortably make this determination.…”
Section: Discussionmentioning
confidence: 99%
“…have done a prospective comparison of the SIMARD MD to overall clinical impression of driving fitness. (1) On the education side of things, Moorhouse and Hamilton have prospectively examined the effect of a campaign designed to address perceived barriers to assessing driving by primary care providers. (2) Hogan et al ., after a modified Delphi procedure, present consensus statements on assessing driving fitness in older adults.…”
mentioning
confidence: 99%
“…Scoring in the indeterminate range was near a 50% chance of passing/failing the road test, similar to the findings of prior studies. ( 18 , 20 ) The high misclassification error rate, regardless of the cut-point used, is further evidenced by the limited AUC (.692). The data show that the SIMARD-MD does not have the ability to accurately distinguish between safe and unsafe drivers, and should not be used as a sole screening tool in drivers with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, Bédard and colleagues ( 19 ) concluded that the SIMARD-MD was vulnerable to an education bias, and may create a structural inequity by failing to account for education in the interpretation of the test results. Moreover, Wernham and colleagues ( 20 ) found no association between SIMARD-MD scores of clients with cognitive impairment and the clinical impressions of their geriatricians regarding fitness-to-drive, further questioning the validity of the test results.…”
Section: Introductionmentioning
confidence: 99%